Model of IT graduate in the conditions of digitalization of the Republic of Kazakhstan - Kazimova, D.A.; Bukh, R.P.; Petryakov, P.A.; Spirina, Ye.A. (KU Publ., 2022)
The article analyzes the model of a graduate of the Faculty of Information Technology on the example of the specialty “Information Systems”. It contains special requirements for the content of training information systems specialists, especially for training new types of IT specialists who are able to contribute and analyze various situations, predict the results of decisions, be creative in finding solutions, and be aware of their personal responsibility. In the graduate model, there are distinguished groups of competencies, such as socio-personal, general professional, and special competencies. The components of the content of the educational program for students of the specialty “Information Systems” are described, which have been finalized and changed under the requirements of modern development of society, the degree of digitalization, legislative and regulatory documents of the Republic of Kazakhstan. The main issues and difficulties of training IT specialists arising from changes in the needs of society, the demand for specialists in this field, as well as the recognition by employers of the quality of graduate training, are identified. The article also emphasizes the importance of such an element of training as professional practice, during which the student will be able to apply his knowledge, skills and abilities acquired during training, as well as personal qualities in accordance with the goals of professional activity.
Қазақстан Республикасының цифрландыру жағдайындағы IT-түлегінің моделі
Модель ИТ-выпускника в условиях цифровизации Республики Казахстан
Keywords: information technologies; informational systems; professional competencies; professional skills; IT-specialist; training specialist in information systems; specialist training modules; model of an IT-graduate; digitalization; training